Impact of Fiscal Policy on Poverty and Inequality in Uganda : Fiscal Incidence Analysis Using the UNHS 2016/17 - Mejia-Mantilla, Carolina (World Bank, Washington, DC, 2019)
This study analyzes the incidence of public revenues (tax collection) and expenditures (including direct and indirect transfers, indirect subsidies, and in-kind transfers) on the level of poverty and inequality in Uganda, using the internationally recognized methodology developed by the Commitment to Equity institute. The results show that Uganda's fiscal policy is moderately equalizing and lowers the Gini coefficient by 3.2 points. The personal income tax, followed by education in-kind transfers, are the biggest contributors to reducing inequality. Although equalizing, fiscal policy is poverty-inducing in Uganda. Direct transfers are pro-poor in distribution but are not large enough to counteract the purchasing power reductions from indirect taxes; the poverty headcount ratio increases by 2.3 percentage points. Going forward, the combination of raising additional revenue by broadening the personal income tax base and removing valued-added tax exemptions while using the additional resources to increase the size and coverage of pro-poor direct transfers programs may alleviate poverty and reduce inequality.